2020
DOI: 10.1101/2020.06.06.20123919
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of strict lock down measures on Covid-19 seroprevalence rate and herd immunity

Abstract: Background: Covid-19 seroprevalence rates and serological tests are important tools in understanding the epidemiology of the disease and help in the fight against it. Seroprevalence rates vary according to the population studied and the test employed and they range from 0.133 to 25.7%. The purpose of this study is to assess the seroprevalence rate in a population of healthy blood donors living under strict lockdown measures in Jordan which has in total 71 confirmed cases per million population. Methods: Left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 6 publications
1
20
1
Order By: Relevance
“…10 In other geographical regions, serosurveys in healthy individuals demonstrated a very low rate of positivity for SARS-CoV-2. [11][12][13][14][15] In our study, we confirm a low rate of antibodies against SARS-CoV-2 on a group of blood donors from a geographical region with a moderate incidence (187 cases/100,000 inhabitants vs the national data of 390 infections/100,000 inhabitants); our results are at variance with those observed in other regions of Italy. In fact, a higher rate of anti-SARS-CoV-2 antibodies has been reported in studies conducted in a region with high incidence of infection, such as Lombardy, the most affected region in Italy, where the seroprevalence in blood donors was 5.2%, a number that is justified by the wide circulation of the virus in that area during the pandemic A limitation of our study is that the enrolled population (18-65 years old) is representative of only a part of the general population, since in Italy 22% of the individuals is aged >65 years (16) However, presented data are relevant in that they refer to the more acting/interacting group of the population, also important from a productive point of view.…”
Section: Italy Registered the First Imported Cases Of Infection In 31supporting
confidence: 71%
“…10 In other geographical regions, serosurveys in healthy individuals demonstrated a very low rate of positivity for SARS-CoV-2. [11][12][13][14][15] In our study, we confirm a low rate of antibodies against SARS-CoV-2 on a group of blood donors from a geographical region with a moderate incidence (187 cases/100,000 inhabitants vs the national data of 390 infections/100,000 inhabitants); our results are at variance with those observed in other regions of Italy. In fact, a higher rate of anti-SARS-CoV-2 antibodies has been reported in studies conducted in a region with high incidence of infection, such as Lombardy, the most affected region in Italy, where the seroprevalence in blood donors was 5.2%, a number that is justified by the wide circulation of the virus in that area during the pandemic A limitation of our study is that the enrolled population (18-65 years old) is representative of only a part of the general population, since in Italy 22% of the individuals is aged >65 years (16) However, presented data are relevant in that they refer to the more acting/interacting group of the population, also important from a productive point of view.…”
Section: Italy Registered the First Imported Cases Of Infection In 31supporting
confidence: 71%
“…France (3%), 17 Italy (5.1%), 18 Denmark (1.8%), 19 and Jordan (0%). 20 In this study, although seven samples were reactive to the initial total antibodies test, no asymptomatic active COVID-19 infection was found because all seven BDs reactive for total antibodies were negative for the viral nucleic acid and IgM antibody against anti-SARS-CoV-2. In addition, only two samples (0.09%) were positive for IgA and IgG antibody tests.…”
Section: Titer Of the Igg Antibody Against Sars-cov-2contrasting
confidence: 49%
“…The seroprevalence in this study, albeit conducted among blood donors who had no confirmed SARS-CoV-2 infection, was consistent with most findings from other studies of the prevalence of anti-SARS-CoV-2 antibodies among blood or plasma donors, or of stored samples, from January to June 2020. Notwithstanding the differences in study methods and SARS-CoV-2 transmission patterns between different areas, most of these studies found low levels of seroprevalence of 0% to 23% ( Erikstrup et al, 2020 , Gallian et al, 2020 , Grzelak et al, 2020 , Filho et al, 2020 , Ng et al, 2020 , Percivalle et al, 2020 , Sughayer et al, 2020 , Thompson et al, 2020 , Valenti et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, 0% seroprevalence was reported in Amman city, Jordan ( Sughayer et al, 2020 ); 0.1% in the San Francisco Bay Area, California, USA ( Ng et al, 2020 ); 0.9% (IgG) in 3 federal states (North Rhine-Westphalia, Hesse, and Lower Saxony) in Germany ( Fischer et al, 2020 ); 1.9% in Denmark ( Erikstrup et al, 2020 ); 2.7% in blood donors in the Netherlands ( Slot et al, 2020b ); 2.7% in 4 departmental areas in France ( Gallian et al, 2020 ); 3.0% in in two blood banks in Clermont and Noyon cities, Oise, France ( Fontanet et al, 2020 ); 3.2% in Scotland ( Thompson et al, 2020 ); 4.0% in the State of Rio de Janeiro, Brazil ( Filho et al, 2020 ); 7.1% in Milan metropolitan area, Lombardy, Italy ( Percivalle et al, 2020 , Valenti et al, 2020 ); and 8.5% (overall weighted adjusted) in England ( Erikstrup et al, 2020 , Gallian et al, 2020 , Grzelak et al, 2020 , Filho et al, 2020 , Ng et al, 2020 , Percivalle et al, 2020 , Sughayer et al, 2020 , Thompson et al, 2020 , Valenti et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%